A non-destructive technique for estimation of amylose, resistant starch and starch in potato using NIR spectroscopy - Alka Joshi; C. Pradeepika; Bandana Kaundal; Pinky Raigond; Brajesh Singh; Bhawna Kaundal (JOURNAL OF ROOT CROPS, 2025)
Abstract The NIRMaster is a bench top Near Infrared Spectroscopy (NIRS) for quantification and identification of the biochemical components at 0.1% level. NIRS generates a characteristic spectrum that is distinct for a given sample and allows identification as well as quantification of its components and it is a non-destructive, rapid method for the determination of biochemical parameters. In this current study about forty-eight potato cultivars were studied for amylose, resistant starch and starch contents respectively to develop calibrated models using NIRMaster. Training and calibration part was done using the fresh produce of potatoes harvested from the Modipuram campus of ICAR-CPRI and validation was done using fresh produce from the same location as well as advance-colored hybrids from Patna center of ICAR-CPRI. The reference predicted values for amylose, resistant starch and starch were in the range of 15.81 to 32.83%, 24.38 to 48.49% and 41.15 to 56.21% respectively. The developed methods showed accuracy in the range of approximately 60-70% for all the targeted parameters. However, accuracy can be further enhanced by expanding the training/ calibration sample sets. The results obtained in this study have shown high applicability of NIR spectroscopy for the measurement of amylose, resistant starch, and starch content for potato samples for quicker estimation.This is the first report being presented on NIR spectroscopy about the nutritional composition of Indigenous potato varieties.